Transcriptome analysis of Phoenix canariensis Chabaud in response to Rhynchophorus ferrugineus Olivier attacks - Giovino, Antonio; Bertolini, Edoardo; Fileccia, Veronica; Al Hassan, Mohamad; Labra, Massimo; Martinelli, Federico (Frontiers in Plant Science, 2015)
Red Palm Weevil (RPW, Rhynchophorusferrugineus Olivier) threatens most palm species worldwide. Until now, no studies have analyzed the gene regulatory networks of Phoenix canariensis (Chabaud) in response to RPW attacks. The aim of this study was to fill this knowledge gap. Providing this basic knowledge is very important to improve its management. RESULTS: A deep transcriptome analysis was performed on fully expanded leaves of healthy non-infested trees and attacked trees at two symptom stages (middle and late infestation). A total of 54 genes were significantly regulated during middle stage. Pathway enrichment analysis showed that phenylpropanoid-related pathways were induced at this stage. More than 3300 genes were affected during late stage of attacks. Higher transcript abundances were observed for lipid fatty acid metabolism (fatty acid and glycerolipids), tryptophan metabolism, phenylpropanoid metabolism. Key RPW-modulated genes involved in innate response mediated by hormone crosstalk were observed belonging to auxin, jasmonate and salicylic acid pathways. Among transcription factors, some WRKYs were clearly induced. qRT-PCR validation confirmed the upregulation of key genes chosen as validation of transcriptomic analysis. CONCLUSION: A subset of these genes may be further analyzed in future studies to confirm their specificity to be induced by RPW infestations.